Brain reserve in hepatic encephalopathy: Pathways of damage and preventive strategies through lifestyle and therapeutic interventions - Jacqueline Cordova-Gallardo; Andres Manuel Vargas-Beltran; Samantha Melanie Armendariz-Pineda; Jesus Ruiz-Manriquez; Javier Ampuero; Aldo Torre (Annals of Hepatology)
Brain reserve is an important concept to understand the variability of damage associated with brain-related diseases and includes the adaptation of cognitive processes to preserve brain function. A good cognitive reserve might delay the onset of clinical manifestations of neurodegenerative diseases as well as hepatic encephalopathy, improving the quality of life in patients with chronic liver diseases. By stimulating activities and maintaining overall health, individuals may be able to enhance their brain's resilience to age-related changes and pathology. This review aims to collect all the data available on the role of brain reserve in hepatic encephalopathy development, and the potential effect of a good brain reserve in slowing down hepatic encephalopathy progression and frequency.